GOOD GOVERNANCE DAN LOYALITAS ANGGOTA PARTAI NASIONAL DAN PARTAI LOKAL DI ACEH - Muhammad Suhery; Permana Honneyta Lubis; T.Roli Ilhamsyah Putra (Jurnal Magister Manajemen, 2017)
Abstract:The purpose of this study is to analyze/test: (1) to describe accountability, transparency, public participation, leadership performance and loyalty of members of national parties and local parties in Aceh is good; (2) the effect of accountability on the performance of party leaders of national and local parties; (3) the effect of transparency on the performance of party leaders of national and local parties; (5) the influence of accountability on the loyalty of members of national parties and local parties, (6) the influence of transparency on the loyalty of members of national parties and local parties, (7) the influence of public participation on the performance of national and local party leaders, Loyalty of members of national parties and local parties (8) the influence of the performance of national and local party leaders on the loyalty of members of national parties and local parties in Aceh and (9) the effect of accountability, transparency, public participation on the loyalty of national party members and local parties in Aceh through Performance of national party leaders and local parties in Aceh. The objects of this research are good governance, performance of national party leaders and local parties, and loyalty of members of national parties and local parties in Aceh. Methods of data analysis in this study using path analysis (Path Analysis), with the number of respondents as many as 81 people. The results showed that accountability was obtained an average value of 3.945, transparency obtained an average value of 4,045, public participation obtained an average value of 3.833, the performance of leadership obtained average value of 3.784 and loyalty cadres of national parties and local parties in Aceh obtained an average score of 4,810, thus it can be explained that this research variable is already running well. While the test results prove that accountability, transparency and public participation significantly influence the performance of leaders of national parties and local parties. Then accountability, transparency and public participation also have a significant influence on the loyalty of members of national parties and local parties.Keywords:   Accountability, Transparency, Public Participation, Leaders Performance and Member LoyaltyAbstrak: Tujuan penelitian ini adalah untuk menganalisis/menguji: (1) mendeskripsikan akuntabilitas, transparansi, partisipasi publik, kinerja pimpinan dan loyalitas anggota partai nasional dan partai lokal di Aceh sudah baik; (2) pengaruh akuntabilitas terhadap kinerja pimpinan partai nasional dan partai lokal; (3) pengaruh transparansi terhadap kinerja pimpinan partai nasional dan partai lokal; (4) pengaruh partisipasi publik terhadap kinerja pimpinan partai nasional dan partai lokal, (5) pengaruh akuntabilitas terhadap loyalitas anggota partai nasional dan partai lokal, (6) pengaruh transparansi terhadap loyalitas anggota partai nasional dan partai lokal, (7) pengaruh  partisipasi publik terhadap loyalitas anggota partai nasional dan partai lokal (8) pengaruh kinerja pimpinan partai nasional dan partai lokal terhadap loyalitas anggota partai nasional dan partai lokal di Aceh dan (9) pengaruh akuntabilitas, transparansi, partisipasi publik terhadap loyalitas anggota partai nasional dan partai lokal di Aceh melalui kinerja pimpinan partai nasional dan partai lokal di Aceh. Adapun yang menjadi objek penelitian ini adalah good governance, kinerja pimpinan partai nasional dan partai lokal, dan loyalitas anggota partai nasional dan partai lokal di Aceh. Metode analisis data dalam penelitian ini menggunakan motode analisis jalur (Path Analysis), dengan jumlah responden sebanyak 81 orang. Hasil penelitian menunjukkan bahwa akuntabilitas diperoleh nilai rata-rata sebesar 3,945, transparansi diperoleh nilai rata-rata sebesar 4,045, partisipasi publik diperoleh nilai rata-rata sebesar 3,833, kinerja pimpinan diperoleh nilai rata-rata sebesar 3,784 dan loyalitas kader partai nasional dan partai lokal di Aceh diperoleh nilai rata-rata sebesar 4,810, dengan demikian dapat dijelaskan bahwa variabel penelitian ini sudah berjalan dengan baik. Sedangkan hasil pengujian membuktikan bahwa akuntabilitas, transparansi dan partisipasi publik berpengaruh secara signifikan terhadap kinerja pimpinan partai nasional dan partai lokal. Kemudian akuntabilitas, transparansi dan partisipasi publik juga mempunyai pengaruh signifikan terhadap loyalitas anggota partai nasional dan partai lokal.Kata kunci:     Akuntabilitas, Transparansi, Partisipasi Publik, Kinerja Pimpinan dan Loyalitas Anggota